My guardian: A personal safety mobile application - Azman F.; Suraya Q.; Rahim F.A.; Mohd M.S.; Mohd Ariffin N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Accident prevention; Mobile computing; Presses (machine tools); Smartphones; Alarm; Dangerous situations; Emergency alerts; Emergency situation; Mobile applications; Personal safety; Text messaging